TRADITIONAL BALINESE DANCE CREATIVITY AS MEDIA OF WORSHIPPING GOD IN HINDU RELIGIOUS PRACTICES - Ria Taurisia Armayani (Widya Sandhi, 2021)
This research aims to study the creativity of Balinese dance which is used as a medium of worshipping God in Hindu practice. This research is designed in an interpretive descriptive type in order to provide an in-depth description of the research focus. There are three findings in this study, namely art as art as an expression of the soul, art as the cultivation of religious values, and art as a means of worshipping God in Hindu life. First, art as an expression of the soul is closely related to the outpouring of feelings through the appearance of works of art that can improve the quality of life. Second, arts as the inculcation of religious values are related to the use of Hindu religious symbols. Third, art as a means of worship is indicated by artistic creativity that is actualized by dance artists as an appreciation of Ida Sang Hyang Widhi Wasa (God Almighty) with his various prabhavas (manifestation of God) in the implementation of Hindu religious rituals. The movements displayed are representations of the mudra sulinggih (gestures of the priest's while performing worship) which are also rhythmic movements that have an association with cosmic dances.